Recent advances in natural products targeting α-synuclein aggregation or clearance in Parkinson's disease - Jay Gupta; Koneni V. Sashidhara (Elsevier, 2023)
Parkinson's disease is a neurodegenerative disorder characterized by the accumulation of misfolded α-synuclein fibrils, leading to the formation of Lewy bodies. Currently, no effective treatment exists to halt the progression of the disease. Only symptomatic relief and dopamine replacement therapy are available, but they are unable to halt the underlying disease process. Therefore, there is an urgent need for targeted drugs that can effectively stop the progression of Parkinson's disease by specifically targeting the aggregation and clearance of α-synuclein through various mechanisms. In this context, natural products have emerged as a promising source of potential therapeutic agents. A significant number of drugs used in the treatment of central nervous system diseases are either natural products or derived from them. In this review, we focus on natural products discovered from 2015 onwards that target the aggregation and/or clearance of α-synuclein using diverse approaches. By exploring these natural compounds, we aim to shed light on their potential as therapeutic interventions for Parkinson's disease.